Herramienta metodológica para el desarrollo de auditorias internas integrales del sistema de gestión de calidad y el modelo estándar de control interno para la Secretaría de Educación Distrital (2009)
The proposed methodology presents an inclusive approach to assess harmoniously and additional requirements of the System of Quality Management for the Public Sector (NTC GP 1000: 2004) and elements of Standard Model Internal Control (MECI 1000: 2005) under the cycle PHVA, as well as the main products to reveal by the auditor.